2022
DOI: 10.1186/s12885-022-09624-y
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitors may reduce the efficacy of ribociclib and palbociclib in metastatic breast cancer patients based on an observational study

Abstract: Introduction Approximately 20–33% of all cancer patients are treated with acid-reducing agents (ARAs), most commonly proton pump inhibitors (PPIs), to reduce gastroesophageal reflux disease symptoms. Palbociclib and ribociclib are weak bases so their solubility depends on different pH. The solubility of palbociclib dramatically decreases to < 0.5 mg/ml when pH is above 4,5 but ribociclibs’ solubility decreases when pH increases above 6,5. In the current study, we aimed to investigate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
(52 reference statements)
1
22
0
1
Order By: Relevance
“…It has been revealed in previous studies that, in metastatic breast cancer patients receiving palbociclib, compared to non-use, concomitant PPI use reduces PFS [17,20]. In addition, these studies demonstrated that concomitant PPI use is an independent risk factor for a shorter PFS [17,20].…”
Section: Discussionmentioning
confidence: 93%
“…It has been revealed in previous studies that, in metastatic breast cancer patients receiving palbociclib, compared to non-use, concomitant PPI use reduces PFS [17,20]. In addition, these studies demonstrated that concomitant PPI use is an independent risk factor for a shorter PFS [17,20].…”
Section: Discussionmentioning
confidence: 93%
“…This appears to be of particular clinical relevance when a dose reduction of ribociclib may be required because of toxicity. Noteworthy, the results from a recently published observational study suggest the opposite conclusion that PPIs may reduce the efficacy of ribociclib in metastatic breast cancer patients [ 21 ]. However, the higher doses of PPIs (twice the drug doses administered in our work) and heterogeneity of drugs used in that work, compared to our study, might partially account for such a difference.…”
Section: Discussionmentioning
confidence: 99%
“…Subgroup analysis carried out in our cohort suggests that PPIs do not affect PFS, regardless of the endocrine resistance or sensitivity. Although a two-way classification (PPI yes/no, endocrine resistance yes/no) may have reduced sample size, such an approach has also been applied in previously published works [ 13 , 21 ]. Other unknown factors that could influence clinical outcomes were a different lifestyle in PPI users compared to non-users, e.g., alimentary disorders or unhealthy conditions associated with worse outcomes in breast cancer, and the lack of information about fed or fasting conditions during PPI administration.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies apostrophize detrimental effects on PFS due to concomitant use of PPIs and CDK 4/6 inhibitors. (5,6) Suppression of gastric acidity changes the composition of the gut microbiome, inducing a higher risk of enteric infections or impaired absorption of some micronutrients. Ergo, the possible direct impact on the impaired response to immunotherapy.…”
Section: I T E R a T U R A / L I T E R A T U R Ementioning
confidence: 99%
“…Nekoliko studija ističe kako istodobno korištenje IPP-ova i CDK 4/6 inhibitora ima negativan utjecaj na vrijeme do progresije bolesti. (5,6) Smanjenjem lučenja želučane kiseline mijenja se sastav crijevnog mikrobioma, mogući je veći rizik enteralnih infekcija te je slabija apsorpcija mikronutijenata. Opisano se pret postavlja uzrokom slabijeg odgovora na imunoterapiju.…”
Section: Sekcija Mladih Onkologa / Young Oncologists Sectionunclassified